Comparing ATPase activity of ATP-binding cassette subfamily C member 4, lamprey CFTR, and human CFTR using an antimony-phosphomolybdate assay - Cui, Guiying; Strickland, Kerry M.; Vazquez Cegla, Analia J.; McCarty, Nael A. (Frontiers in Pharmacology, 2024)
Introduction: ATP-binding cassette (ABC) transporters use the hydrolysis of ATP to power the active transport of molecules, but paradoxically the cystic fibrosis transmembrane regulator (CFTR, ABCC7) forms an ion channel. We previously showed that ATP-binding cassette subfamily C member 4 (ABCC4) is the closest mammalian paralog to CFTR, compared to other ABC transporters. In addition, Lamprey CFTR (Lp-CFTR) is the oldest known CFTR ortholog and has unique structural and functional features compared to human CFTR (hCFTR). The availability of these evolutionarily distant orthologs gives us the opportunity to study the changes in ATPase activity that may be related to their disparate functions. Methods: We utilized the baculovirus expression system with Sf9 insect cells and made use of the highly sensitive antimony-phosphomolybdate assay for testing ATPase activity of human ABCC4 (hABCC4), Lp-CFTR, and hCFTR under similar experimental conditions. This assay measures the production of inorganic phosphate (Pi) in the nanomolar range. Results: Crude plasma membranes were purified, and protein concentration, determined semi-quantitatively, of hABCC4, Lp-CFTR, and hCFTR ranged from 0.01 to 0.36 µg/µL. No significant difference in expression level was found although hABCC4 trended toward the highest level. hABCC4 was activated by ATP with the equilibrium constant (Kd) 0.55 ± 0.28 mM (n=8). Estimated maximum ATPase rate (Vmax) for hABCC4 was about 0.2 nmol/µg/min when the protein was activated with 1 mM ATP at 37 °C (n=7). Estimated maximum ATPase rate for PKA-phosphorylated Lp-CFTR reached about half of hCFTR levels in the same conditions. Vmax for both Lp-CFTR and hCFTR were significantly increased in high PKA conditions compared to low PKA conditions. Maximum intrinsic ATPase rate of hABCC4 was twice that of hCFTR when activated in 1 mM ATP. Conclusion: The findings here suggest that while both ABCC4 and hCFTR bear one consensus and one degenerate ATPase site, the hCFTR exhibited a reduced intrinsic ATPase activity. In addition, ATPase activity in the CFTR lineage increased from Lp-CFTR to hCFTR. Finally, the studies pave the way to purify hABCC4, Lp-CFTR, and hCFTR from Sf9 cells for their structural investigation, including by cryo-EM, and for studies of evolution in the ABC transporter superfamily.